Construção de um aplicativo para estimar risco hipertensivo em adolescentes com histórico familiar de hipertensão, associado a polimorfismos do sistema renina angiotensina aldosterona e as possíveis alterações autonômicas cardíacas - DIAS FILHO, Carlos Alberto Alves (2023)
Introduction: Systemic arterial hypertension (SAH) is a chronic-degenerative disease with a multifactorial origin. With high prevalence around the world. Younger individuals, specifically adolescents, are not exempt from acquiring this pathology, being caused by environmental and genetic factors responsible for physiological changes leading to the development of comorbidities. Aim: Analyzing the hypertensive risk of adolescents with and without a family history of hypertension, associated or not with polymorphisms of the Aldosterone Renine Angiotensin System and the possible autonomic changes may mean the tool created for this purpose. Methods: this is an analytical and cross-sectional study that included 288 adolescents between 11 and 18 years of age from a public school in São Luís - MA. The sample was divided by the family history of arterial hypertension and later by the presence of one of the polymorphisms of the aldosterone renine angiotensin system. Where the characterization parameters, autonomic parameters, genetic parameters and programming of an application that makes use of the variables to estimate hypertensive risk were evaluated. Results: As the first findings in relation to the division of normotensive children and children of hypertensive patients, it was possible to notice negative changes for the second group regarding weight, such as systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR), in addition to lower cardiac variability indicated by specific markers, including HF%, LF% and LF/HA. After the divisions, taking in consideration the polymorphisms, it was also possible to observe negative changes in systemic blood pressure and as one of the main findings, child of hypertensive patients (PHF), together with the presence of one of the POLYMORPHISMS of THE, AGT or at1 receptor of angiotensin 2, presented a lower cardiac autonomic modulation, I feel an important indicator for hypertensive risk. Conclusion: It was possible to show a higher hypertensive risk factor for adolescents. When there was a relationship between the groups of normotensive child and son of hypertensive patients mainly when related to the presence of one of the polymorphisms of the aldosterone renine angiotensin system. That indicated alterations in SBP, DBP, HR, and heart rate variability regarding the time and frequency domain. the risk was more evident especially when the groups had a family history with the presence of polymorphic homozygous alleles.